PERANCANGAN SISTEM ANTRIAN ANTI COVID 19 BERBASIS INTERNET of THINGS MENGGUNAKAN RASPBERRY Pi W ZERO - Laksmana, Agum; Amir, Ardi; Sollu, Tan Suryani; Indrajaya, Muhammad Aristo (Foristek, 2022)
Utilization of electronic technology in various aspects of human life, both in household needs, education, industry, and human habitation itself. In this discussion is how to design a queuing system based on the Internet of Things using a Raspberry Pi W Zero controller. Internet of Things is a concept in which an object or object is implanted with technologies such as sensors and software with the aim of communicating, controlling, connecting, and exchanging data through other devices while still connected to the internet. In designing this queuing system, a website is needed to support this tool to make it easier for users to register online without having to manually take queue numbers. The programming language used for the Raspberry Pi W Zero controller uses python. Testing this queuing system 100% went well and according to what was designed for the design of an Internet of Things based anti covid 19 queuing system using the Raspberry Pi W Zero. With this tool, it can make it easier for users to register queue numbers and be able to run the appropriate Health protocol system.